The current status and influencing factors of diabetes knowledge among non-endocrinology nurses of tertiary general hospitals: a cross-sectional survey study - Jia Song; Su Li; Chongcai Gu; Shiyan Zhao; Xing Li; Siqin Liu; Jinmei Tuo; Shiming Huang (BMC Nursing)
Abstract Background Every year, more than one-third of diabetes patients experience various acute and chronic complications, leading to the presence of diabetes patients in various departments of the hospital. High-quality nursing care can delay the progression of diabetes and effectively reduce the incidence of complications. Therefore, understanding the level of diabetes knowledge and training needs of clinical nurses is of great significance. This survey aims to understand the level of diabetes knowledge and influencing factors of nurses, providing a reference for conducting clinical training. Methods An online cross-sectional survey using a questionnaire and involving 3117 nurses from 9 tertiary general hospitals from Guizhou Province, China were conducted. This questionnaire consists of three parts: a general information survey, self-assessment of diabetes knowledge, and objective assessment of diabetes knowledge. We analyzed the data using SPSS 29.0. Results The participants’ self-assessment score for diabetes knowledge were (62.27 ± 16.80)(out of 100), objective score for diabetes knowledge were (57.33 ± 25.78)(out of 100). Multiple linear regression analyses indicated that diabetes in-service education, department and the last time they cared for a diabetes patient were the influencing factors of nurses’ diabetes knowledge scores (P < 0.05). Conclusion The knowledge of non-endocrinology nurse’ diabetes needs to be improved. There is a gap between non-endocrinology nurses’ self-perception of diabetes knowledge and their actual knowledge level. Therefore, nursing managers should prioritize diabetes knowledge training for nurses in non-endocrinology departments, develop practical training programs based on nurses’ needs, enhance their diabetes care knowledge, and provide higher quality care services to patients.